Nematicidal compounds of Peperomia japonica. (October 2018) - Nagashima, Kazumi; Yamano, Yoshi; Sugimoto, Sachiko; Ishiwata, Kenji; Kanuka, Hirotaka; Otsuka, Hideaki; Matsunami, Katsuyoshi
Graphical abstract: Highlights: Peperomia japonica exhibited toxic effects toward Caenorhabditis elegans . One new polyketide (1 )and two new secolignans (2, 3 ) were isolated. Compounds1 and2 showed lethal activity toward Heligmosomoides polygyrus . These compounds can be used for developing new antiparasitic agents. Abstract: On antiparasitic screening, we found that extracts of Peperomia japonica have nematicidal activity. Bioassay-guided fractionation of the methanolic extract resulted in the isolation of one new polyketide (1 ), two new seco-lignans (2, 3 ), and two known polyketides (4, 5 ). The structures of these compounds were established by extensive one- and two-dimensional nuclear magnetic resonance spectroscopy and high-resolution electrospray ionization mass spectrometry analyses. Compounds1 and4 show strong lethal activity toward Caenorhabditis elegans and Heligmosomoides polygyrus.